Urological Aspects in Patients with Alkaptonuria: A Case-Control Study. Issue 5 (October 2020) - Suoub, Mohammed; Alsbou, Mohammed; Sawaqed, Fadi
This study aimed to evaluate the urinary tract for dynamic function and stones and calcifications in patients with alkaptonuria. Thirty-eight patients were prospectively divided into two groups. Study group (A) involved 17 patients; the average age was 42 years. The control group (B) involved 21 patients; the average age was 37 years. All patients from the two groups underwent uroflowmetry assessment and ultrasonography for the kidneys and urinary bladder, and prostate in two phases (full bladder and empty bladder). Group A—Bladder volume ranged between 400 and 520 cc. The peak flow rate was between 7 and 23 mL/s, with an average of 18.6 mL/s. Flow rate curves shape were acceptable to the normal bell-shape curve in 11 patients. Seven patients (41%) had prostate calcification accounting for 5%–35% of prostate size. Group B—Bladder volume ranged between 290 and 510 cc. The peak flow rate was 8–27 ml/s, with an average of 20 mL/sec. Normal bell shape voiding curves were observed in 17 patients (80%). Four patients (19%) had prostate calcification accounting for 2%–12% of prostate size. Renal measurements on ultrasonography were the same in both groups. Patients with alkaptonuria developed prostate calcification at younger age; they have a slight but not statistically significant reduced peak urinary flow rate and post void residual urine.